Mengevaluasi Kebijakan Diplomasi Perlindungan WNI melalui Paradgma “Duty of Care” [Evaluating Indonesia’s Diplomacy Policy for The Protection of Indonesian Citizens Abroad Through The “Duty of Care” Paradigm] - Surwandono, S; Nugroho, Ariyanto (Jurnal Politica, 2022)
Diplomacy in the protection of Indonesian citizens (WNI) requires serious attention related to the large number and complexity of protection that must be provided by the Indonesian government. This condition requires the Indonesian government to provide a number of superstructures as a legal basis for protection, as well as infrastructure as a means of implementing policies effectively. This article wants to evaluate the governance of the protection of Indonesian citizens within the framework of the “Duty of Care” (DoC) paradigm as a cosmopolitan idea in upholding human security outside the jurisdiction of a country. The data sources was taken from official documents from the Directorate of Protection of Indonesian Citizens, Permenlu No. 5 of 2018, the Strategic Plan for the Protection of Indonesian Citizens, as well as news in a number of mass media that informed the dynamics of problems and the protection of Indonesian citizens abroad. This article finds that Indonesia has adopted the structure of the Idea of DoC in the roadmap for the protection of Indonesian citizens, both in the Social Contract of Care, Intermediaries of Care, and the Extension of Care model although it is still artificial and not yet simultaneous. A policy breakthrough from the Indonesian government is needed to build a more substantive and progressive protection policy superstructure in the form of increasing the policy level from the Minister of Foreign Affairs Regulation to the Act and improving the quality and quantity of Indonesian citizen protection infrastructure so that the reach of protection will be wider, responsive and articulate in providing the best protection for Indonesian citizens abroad.AbstrakDiplomasi perlindungan warga negara Indonesia (WNI) memerlukan perhatian yang serius terkait dengan besarnya jumlah dan kompleksitas perlindungan yang harus diberikan oleh pemerintah Indonesia. Kondisi ini mengharuskan pemerintah Indonesia untuk menyediakan sejumlah suprastruktur sebagai landasan hukum melakukan perlindungan, maupun infrastruktur sebagai sarana mengimplementasikan kebijakan secara efektif. Artikel ini hendak mengevaluasi tentang tata kelola perlindungan WNI dalam kerangka besar paradigma “Duty of Care” (DoC) sebagai gagasan yang kosmopolitan dalam menjunjung tinggi keamanan manusia di luar yurisdiksi suatu negara. Sumber data yang dianalisis berasal dari dokumen resmi dari Direktorat Perlindungan WNI, Permenlu No. 5 Tahun 2018, dokumen Rencana Strategis Perlindungan WNI, serta berita di sejumlah media massa yang menginformasikan dinamika problem dan perlindungan WNI di luar negeri. Artikel ini menemukan bahwa Indonesia telah mengadopsi struktur gagasan DoC dalam peta jalan perlindungan WNI, baik dalam model social contract of care, intermediaeries of care, dan extension of care model, meskipun masih bersifat artifisial dan belum simultan. Diperlukan terobosan kebijakan dari pemerintah Indonesia untuk membangun suprastruktur kebijakan perlindungan yang lebih substantif dan progresif dalam bentuk peningkatan level kebijakan dari basis Peraturan Menteri Luar Negeri ke Undang-Undang dan peningkatan kualitas dan kuantitas infrastruktur perlindungan WNI sehingga daya jangkau perlindungan akan menjadi lebih luas, responsif dan artikulatif dalam memberikan perlindungan yang terbaik bagi WNI di luar negeri.